Numerical Calculation Study on the Correlation Law Between Shot Peening Process Parameter and Gear Surface Roughness - Yalin Tang; Jiuyue Zhao; Jinyuan Tang (Jixie chuandong)
In addition to affecting the residual stress field on the gear surface, shot peening also changes the surface roughness of the gear. The surface roughness at the tooth root and the pitch circle will strongly affect its service performance. Therefore, it is necessary to study the evolution process of the gear surface roughness during the shot peening process. In this study, a random shot finite element model is established to simulate the shot peening process in the vicinity of the root and the pitch circle, and all discrete data in the impact region are extracted to calculate the surface roughness parameters. The results obtained by numerical simulation are basically consistent with the test results after gear shot peening. Subsequently, the effects of shot peening time, shot size and impact velocity on the surface roughness parameters near the root and the pitch circle are studied. The blasting process parameters can be reasonably selected to achieve the purpose of controlling the surface roughness of the gear after shot peening. The research shows that, under the same shot peening parameters, the surface roughness Ra and Rz values of the pitch circle are significantly smaller than the root. The surface roughness increases at the root with the increase of the impact velocity and the diameter of the shot, the Ra and Rz increase obviously and the impact of the shot diameter on the roughness parameter is greater than the impact velocity. With the increase of the impact velocity and the diameter of the shot, the surface roughness Ra and Rz of the indexing circle increase significantly, and the Rmr(-1) value decreases. And the effect of the diameter of the shot on the roughness parameter is greater than the impact velocity.